How good governance affects performance accountability in a local government - Hama, Aloisius; Sriyana, Jaka; Afandi, Akhsyim (Asian Development Policy Review, 2026)
This research aims to explore the impact of Good Governance on Performance Accountability, mediated by Accounting Information Systems (AIS) and Bureaucratic Reform within the Manggarai Regency Government, Indonesia. Data were collected through questionnaires distributed to public officials in the local government and analyzed using the Partial Least Squares (PLS) method. The results indicate that Good Governance significantly and positively affects AIS (β = 0.698, p = 0.000), bureaucratic reform (β = 0.646, p = 0.000), and performance accountability (β = 0.316, p = 0.035). Furthermore, Good Governance positively influences Performance Accountability through the AIS channel (β = 0.200, p = 0.044) and the Bureaucratic Reform channel (β = 0.371, p = 0.000). This underscores that implementing Good Governance principles can enhance the effectiveness and efficiency of AIS utilization and promote structural and systemic reforms in the bureaucracy, ultimately leading to improved performance accountability. The outcomes of this study offer valuable theoretical and practical insights, affirming the essential role of Good Governance in enhancing the accountability of local government performance. This research may serve as a foundation for formulating improved policies and practices in local governance, thereby enhancing governance quality and public service delivery.